Scoping Review of Technology Enabled Healthcare Integration - Towards Sustainable Care - Loncar-Turukalo, Tatjana; Zdravevski, Eftim; Madevska Bogdanova, Ana; Solarevic, Milica; Lehocki, Fedor; Trajkovikj, Vladimir (IEEE, 2025)
Technology serves as a relevant facilitator in integration of care, supporting healthcare across many pillars, such as diagnoses, drug-development, administration and coordination of services, but as well playing a pivotal role in disease prevention and pervasive health monitoring. This study presents the scoping review of the literature corpus related to technology trends supporting healthcare integration. The study explores 5 digital libraries from major publishers, aiming to identify changes in research trends in the decade from 2014 to 2024, and investigate which implementation challenges, barriers and risks present the major focus in healthcare integration. In total 14721 relevant studies were identified and included in collating and summarizing of the results in this work. The study shows that there is a triple increase in the number of studies from 2020 onwards, mainly focused on technology and implementation challenges. The main topic of the studies shifts from Internet of Medical Things (IoMT) until 2019 to AI in healthcare, which gained its momentum by continual advances in AI performance across different tasks. Enhanced health care, holistic care and patient experience are the most targeted benefits and opportunities of integrated care, while security and privacy of health related data remain the main concerns and playground for further research.
Keywords: Internet of Medical Things; integrated healthcare; scoping review; security; privacy